Utilization of Foxtail Millet (Setaria italica) from Papua as an Alternative Feedstuff to Substitute Corn - Tirajoh, Siska (Indonesian Animal Sciences Society, 2015)
Papua foxtail millet (Setaria italica) is a plant which has been used as a source of carbohydrate, but it has not been used optimally. High demand in consuming corn as a poultry feeds provides an opportunity for Papua foxtail millet to be used as a substitute for corn in feed. Evaluation of nutritive values and antinutrient shows that Papua foxtail millet potential to be used as feed stuff. Studies on cultivation technology, evaluation of the nutritive values and antinutrient and its benefits as an alternative feed are relatively limited. The results shows that the Papua foxtail millet contains dry matter (88.37%), ash (0.86%), protein (12.07%), fat (2.76%), crude fiber (1.93%), metabolizable energy (3,139 kcal/kg) and anti-nutritional factors (3.07% of phytate and 0.01% of tannins). Several studies reported that the use of Papua foxtail millet at various levels (25-100%) in feed, can substitute corn and give a positive response on consumption, daily weight gain, feed conversion, carcass composition and percentages and egg production. It can be concluded that the Papua foxtail millet can be used as a corn substitution in poultry feed. Key words: Papua foxtail millet, nutritive values, antinutrition, alternative feedÂ Â